Analysis The Power of Love in Rachel Ward’s Novel Numbers - Amirudin, Andy; Dohude, Pasniat (Jurnal Ilmiah Pendidikan Scholastic, 2024)
The title of this research is "Analysis of the Power of Love in Rachel Ward's Novel Numbers". This research problem focuses on personality, the power of love, and the external conflict experienced by Jemma as reflected in the novel Numbers. The technique used in this research is literature. To obtain certain data by searching and collecting several books related to magical analysis of personality, the power of love, and external conflict in a literary work. By quoting sentences or words that show personality characteristics, the power of love, and external conflicts and then describing them. Personality According to Sigmund Freud includes three parts, namely Id, Ego, and Superego. This happens because Jemma lives as a human who has a different personality. The power of love occurs because the human characters in the novel interact with other humans, giving rise to feelings of joy, care, responsibility, sexual feelings. External conflict is divided into two, namely conflict between a person and another person, a person and a group and also a conflict between a person and his country. External conflict occurs because Jemma integrates with other humans, causing conflict between Jemma and other people, while Jemma's conflict with his country is when there is a bombing at the London which makes them considered terrorists and all the police in their country are looking for them. From this novel, lessons can be learned such as the struggle for life, in life, don't give up even though the obstacles you face are so big. Continue to be good people and always strengthen each other.